A pilot randomised controlled trial of the management of systolic blood pressure during endovascular thrombectomy for acute ischaemic stroke. (12th December 2019) - Deng, C.; Campbell, D.; Diprose, W.; Eom, C.; Wang, K.; Robertson, N.; Short, T. G.; Brew, S.; Caldwell, J.; McGuinness, B.; Barber, P. A.
Summary: It is unknown whether systolic blood pressure augmentation during endovascular thrombectomy improves clinical outcomes. This pilot randomised controlled trial aimed to assess the feasibility of differential systolic blood pressure targeting during endovascular thrombectomy procedures for anterior circulation ischaemic stroke. Fifty‐one eligible patients fulfilling the national criteria for endovascular thrombectomy were randomly assigned to receive either standard or augmented systolic blood pressure management from the start of anaesthesia to recanalisation of the target vessel. Systolic blood pressure targets for the standard and augmented groups were 130–150 mmHg and 160–180 mmHg, respectively. The study achieved all feasibility targets, including a recruitment rate of 3.5 participants per week and median (IQR [range]) of mean systolic blood pressure separation between groups of 139 (135–143 [115–154]) vs. 167 (150–175 [113–188]) mmHg, p < 0.001. Data completeness was 99%. Independent functional recovery at 90 days (modified Rankin Scale 0, 1 or 2) was achieved in 30 (59%) patients, which is consistent with previously published data. There were no safety concerns with trial procedures. In conclusion, a large randomised controlled efficacy trial of standard vs. augmented systolic blood pressure management during endovascular thrombectomy is feasible.